Etiology of cutaneous leishmaniasis and anthropophilic vectors in Juruti, Pará State, Brazil Etiologia da leishmaniose cutânea e vetores antropofílicos em Juruti, Estado do Pará, Brasil - Lourdes Maria Garcez; Daniela Cristina Soares; Anadeiva Portela Chagas; Gilberto César Rodrigues de Souza; Jefferson Francisco Correia Miranda; Habib Fraiha; Lucile Maria Flöeter-Winter; Heloísa Marceliano Nunes; Ricardo Andrade Zampiere; Jeffrey Jon Shaw (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2009)
In a preliminary study in Juruti, a mining municipality in western Pará State, Brazil, 12 out of 21 patients suspected of presenting cutaneous leishmaniasis showed positive PCR (SSUrDNA and G6PD): Leishmania (Viannia) braziliensis (9/12; 75%) and L. (V.) sp. (3/12; 25%). Entomological studies in the same location revealed the presence of 12 different phlebotomine species (n =105). One of the most common species was Lutzomyia (Psychodopygus) complexa (17%) which is both highly anthropophilic and a known vector of L. (V.) braziliensis in other regions of Pará. These preliminary findings should serve to guide future epidemiological surveillance in Juruti. Em um estudo preliminar em Juruti, um município minerário na região oeste do Estado do Pará, Brasil, 12 de 21 pacientes suspeitos de possuírem leishmaniose cutânea tiveram PCRs positivas (SSUrDNA e G6PD): Leishmania (Viannia) braziliensis (9/12; 75%) e Leishmania (Viannia) sp. (3/12; 25%). Estudos entomológicos na mesma localidade revelaram a presença de 12 diferentes espécies de flebotomíneos (n = 105). Uma das espécies mais comuns foi Lutzomyia (Psychodopygus) complexa (17%) que é altamente antropofílica e reconhecida vetora de L. (V.) braziliensis em outras regiões do Estado do Pará. Esses resultados preliminares servem como orientação para futura vigilância epidemiológica em Juruti.